2018
DOI: 10.1158/1535-7163.mct-17-0541
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and Carfilzomib Synergistically Inhibit the Proliferation, Survival, and Metastasis of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and deadly human cancers. The 5-year survival rate is very low. Unfortunately, there are few efficacious therapeutic options. Until recently, Sorafenib has been the only available systemic drug for advanced HCC. However, it has very limited survival benefits, and new therapies are urgently needed. In this study, we investigated the anti-HCC activity of carfilzomib, a second-generation, irreversible proteasome inhibitor, as a single agent and in combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Given the mediocre clinical efficacy of sorafenib alone in patients with HCC, it is hoped that its efficacy may be enhanced by combining it with another intervention (34). Previously, carfilzomib has been shown to work synergistically with sorafenib in inhibiting the proliferation, survival and metastasis of HCC cells in vitro (35). Here, we showed that pimozide can enhance the proliferative inhibition of sorafenib in HCC cells, suggesting that it has the potential to improve HCC outcomes as an adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the mediocre clinical efficacy of sorafenib alone in patients with HCC, it is hoped that its efficacy may be enhanced by combining it with another intervention (34). Previously, carfilzomib has been shown to work synergistically with sorafenib in inhibiting the proliferation, survival and metastasis of HCC cells in vitro (35). Here, we showed that pimozide can enhance the proliferative inhibition of sorafenib in HCC cells, suggesting that it has the potential to improve HCC outcomes as an adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is the priority drug used for advanced hepatocellular carcinoma (HCC) [65], as it inhibits the lung metastasis of HCC mediated by CD90 + cancer stem cells (CSCs) [66]. The combination of sorafenib and carfilzomib synergistically suppresses the metastasis of HCC via inducing tumor cell apoptosis [67]. Sorafenib may benefit patients with metastatically differentiated thyroid cancers that are resistant to radioactive iodine [68].…”
Section: Tyrosine Kinase Inhibitor Therapymentioning
confidence: 99%
“…At this point, a previous study also revealed that Wnt7a obviously reduced the cell viability of cervical cancer [9], which shows no difference from our results. The migration ability of liver cancer cells is the primary factor that results in decreased survival rate of HCC patients [27]. Using transwell assay, we revealed that WNT7A overexpression inhibited tumor cell migration.…”
Section: Discussionmentioning
confidence: 99%